2018
DOI: 10.15547/tjs.2018.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of stability and adaptation of cotton genotypes using gge biplot method

Abstract: This research was conducted to study effects of G × E interaction on 38 selected genotypes of cotton with two commercial cultivars Golestan and Sepid (control) in a randomized complete block design with three replications at three locations in Golestan Province in 2014-15. The measured characteristics were included: plant height, sympodial length, sympodial number, boll number, boll weight, seed cotton yield and earliness. Analysis of variance showed that genotype effect is significant in 1 or 5% probability l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 5 publications
(6 reference statements)
1
7
0
Order By: Relevance
“…Linear) was highly significant for all traits, and this indicates that the response to different environments is genetically controlled. This was confirmed by [4] and [15].…”
Section: Resultssupporting
confidence: 80%
“…Linear) was highly significant for all traits, and this indicates that the response to different environments is genetically controlled. This was confirmed by [4] and [15].…”
Section: Resultssupporting
confidence: 80%
“…Many researchers used these methods to evaluate the stability and adaptability of different cotton genotypes (commercial cultivars, new varieties, promising lines, hybrids and their parents) across environments to select the superior and adaptable ones (Balakrishna et al, 2016;Chinchane еt al., 2018;Deho et al, 2021;Dewdar, 2013;Fathi et al, 2018;Güvercİn et al, 2017;Iqbal еt al., 2018;Khalifa et al, 2010;Patil et al, 2017;Shashibhushan & Patel, 2020). Vavdiya et al (2021) used the regression parameters (bi) (S 2 di) to evaluate the stability of 50 "line × tester" (10 × 5) crosses, at three different sowing dates.…”
Section: Introductionmentioning
confidence: 99%
“…The AMMI method and the GGE bi-plot model were often used to analyze experimental data from different ecological experiments and compare the results (Farias et al, 2016;Maleia et al, 2017;Moiana et al, 2014;Orawu et al, 2017;Pretorius et al, 2015;Riaz et al, 2019). The biplot analysis was used to examine the genotype (G) and the genotype × environment interaction (GE) (Farias et al, 2016;Fathi Sadabadi et al, 2018;Yan and Kang, 2003) and to test environments and megaenvironments (Xu et al, 2014). Shahzad et al (2019) tested 41 genotypes (11 inbred lines and 30 intraspecific cotton hybrids) in 6 different environments using the AMMI method to analyze and compare the results.…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Omrani, et al 38 the first four components explained 83% of the GEI. Fathi, et al 39 reported the contribution of the first and second PCs of the GEI as 49.49% and 22.50%, respectively, and both accounted for 71.60% of the variations in the GEI. In another study using AMMI model, the first IPC was significant and explained about 63% of GEI variation 34 .…”
Section: 1| Additive Main Effects and Multiplicative Interaction (Ammi)mentioning
confidence: 99%